Clinical and radiological characteristics of patients with pulmonary marginal zone lymphoma: A single center analysis. (26th May 2020) - Husnain, Muhammad; Kuker, Russ; Reis, Isildinha M.; Iyer, Sunil Girish; Zhao, Wei; Chapman, Jennifer R.; Vega, Francisco; Lossos, Izidore S.; Alderuccio, Juan Pablo
Abstract: Pulmonary marginal zone lymphoma (PMZL) is the most common non‐Hodgkin lymphoma affecting the lung. PMZL is usually an indolent disease. Clinical and radiological variables associated with shorter survival are largely unknown and no consensus exists on preferred treatment strategy in PMZL. Herein we aimed to identify clinical and radiological features associated with shorter survival and inferior treatment outcomes. Forty patients with PMZL were analyzed. FDG‐avid disease was evident in most patients (93%) with staging PET/CT (n = 15). With a median follow‐up in treated patients (n = 38) of 8.4 years (range 0.07‐18.44), the median progression‐free survival (PFS) and overall survival (OS) were 7.5 years (95% CI 1.8‐9.5) and 15.7 years (95% CI 9.3‐NE) respectively. Shorter PFS was observed in patients who presented at diagnosis with elevated LDH, B symptoms, advanced stage and failed to achieve complete response (CR) after initial treatment. Patients with multifocal lung disease, extrapulmonary MZL and cavitary lesions on CT scans exhibited shorter PFS. Nevertheless, no clinical or radiologic findings were associated with shorter OS. All patients treated with surgery (n = 4) and radiation therapy (n = 3) achieved and remained in CR. No higher grade transformations occurred during the follow‐up period. PMZL exhibited excellent outcomes with a 15‐year PMZL‐related OS of 94.9% (95% CI: 81.25%‐98.7%). Radiation therapy and surgery are potentially curative strategies in localized PMZL. Abstract : Elevated LDH, B symptoms, advanced stage and failure to achieve complete response after initial treatment are clinical variables associated with shorter progression‐free survival (PFS) in pulmonary marginal zone lymphoma (PMZL). Multifocal lung disease, extrapulmonary MZL and cavitary lesions on computed tomography scans have been identified as radiologic features associated with shorter PFS. Radiation therapy and surgery are potentially curative strategies in PMZL.